PENGELOLAAN ARSIP ELEKTRONIK DALAM PROSES ADMINISTRASI: KESIAPAN DAN PRAKTEK: Array - Widiatmoko Adi Putranto; Astiti Nareswari; Karomah Karomah (Jurnal Kearsipan, 2018)
Electronic records management is often simply understood as digitization. But failure comes over whenever on one side cultural and social factor are being less recognized and on the other side functions are being less understood. Although the technological infrastructure have been existing in many public institutions. In fact despite having its digital form, the files used in daily routine require wet-ink signatures and revisions on the physical documents. The implementation is less-succeed because it fails to articulate accountability. This research will elaborate a few of case studies, surveys, interviews and literature reviews. Further, this research discusses the need for improvement of digitization and electronic records management.